2016
DOI: 10.21767/2254-6081.100099
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor: Breast Cancer Development and Immunotherapy

Abstract: Breast cancer is well known leading causes of mortality in the females. Current studies have suggested that the imbalances in inflammatory and immune-associated proteins may also give rise to breast cancer and disease progression. Toll like receptors (TLRs) are essential components of innate immune system that protect the host against bacterial and viral infection. It not only express in innate immune cell, its expression also found in breast cancer cells. Activation of TLRs leads to the activation of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[13,14] It was revelad that TLR9 assists in the progression of BC and patients with BC have higher circulating levels of TLR9 compared to normal. [11,13] In their study, González-Reyes et al [3] suggested that BCs with high TLR9 expression by fibroblast-like cells were associated with low probability of metastasis. In contrast, Jukkola-Vuorinen et al [5] revealed that BCs metastasized to axillar lymph nodes at the time of diagnosis had slightly higher TLR9 expression compared with tumors with no axillary lymph node metastasis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[13,14] It was revelad that TLR9 assists in the progression of BC and patients with BC have higher circulating levels of TLR9 compared to normal. [11,13] In their study, González-Reyes et al [3] suggested that BCs with high TLR9 expression by fibroblast-like cells were associated with low probability of metastasis. In contrast, Jukkola-Vuorinen et al [5] revealed that BCs metastasized to axillar lymph nodes at the time of diagnosis had slightly higher TLR9 expression compared with tumors with no axillary lymph node metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that cancer and inflammation are related entities, consequently, persistent inflammatory events can lead to carcinogenesis. [3,[9][10][11][12] In the current literature, several studies exist to investigate relation of TLRs with both inflammation and cancer. TLRs are important components of the innate immune system not only defense host against several infectious agents, but also shown to be expressed by many epithelial tumor cells including BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation